Continuing education for managers as the basis of innovation economy (experience of the Russian Presidential Academy of National Economy and Public Administration) - Safronova, Natalia; Kosareva, Elena (Serbian Journal of Management, 2015)
The experience of establishing a system of continuing education at the Russian Presidential Academy of National Economy and Public Administration (RANEPA) to support the institutional reform of the Russian economy was investigated. A review of the scientific research activities carried out by the Academy was provided. The role of the Academy in the formation of the educational space was demonstrated. The practice of creation of education and training cluster within a structural division of the Academy – the Institute of Sectorial Management – was evaluated as an example.